2019
DOI: 10.1002/pi.5814
|View full text |Cite
|
Sign up to set email alerts
|

The effect of poly(butylene succinate) content on the structure and thermal and mechanical properties of its blends with polylactide

Abstract: Poly(butylene succinate) (PBS) and polylactide (PLA) were blended in a co-rotating twin-screw extruder with various contents of PBS from 0 to 100 wt%. The effect of PBS content on the thermal and mechanical properties of PBS/PLA blends was investigated by using DSC, softening point measurements, a Charpy impact test and tensile testing. The Fourier transform infrared spectra showed that the polymers are immiscible, but the addition of PBS could modify the PLA structure in PBS/PLA blends by changing the content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 16 publications
8
54
0
Order By: Relevance
“…Flexibility and resilience Cannot crystallize to any significant degree, wide melting point, low elastic modulus and stiffness [46] Polybutylene succinate (PBS) direct esterification of succinic acid with 1,4-butanediol Compostable, high flexibility and excellent thermal stability Stiffness and melt viscosity for processing are often insufficient for various end-use applications [47,48] photodegradative, microbial and enzymatic. The objective of this review is to identify the research areas of PLA degradation mechanisms with a focus on hydrolytic, photodegradative, microbial and enzymatic degradation.…”
Section: Starch and Plasticizers Low Costmentioning
confidence: 99%
“…Flexibility and resilience Cannot crystallize to any significant degree, wide melting point, low elastic modulus and stiffness [46] Polybutylene succinate (PBS) direct esterification of succinic acid with 1,4-butanediol Compostable, high flexibility and excellent thermal stability Stiffness and melt viscosity for processing are often insufficient for various end-use applications [47,48] photodegradative, microbial and enzymatic. The objective of this review is to identify the research areas of PLA degradation mechanisms with a focus on hydrolytic, photodegradative, microbial and enzymatic degradation.…”
Section: Starch and Plasticizers Low Costmentioning
confidence: 99%
“…[ 195,196 ] Tensile properties represent physical performance such as tensile strength, elongation at break and tensile modulus of the materials which will influence the physical capability under critical and extreme circumstances. [ 6,197,198 ] For the past few years, numerous studies have been performed on nanocellulose reinforced PLA bionanocomposites, and tensile testing was used to characterize their performance. [ 29,42,102,108,129,146,185,187,192,199,200 ]…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…However, the blending technique is the common method adopted to overcome the PLA brittleness making it useful in those applications (like film production) where high flexibility and toughness are requested. In literature different successful studies can be found where PLA was blended, in different quantities, with other biodegradable polymers such as: polycaprolactone [ 11 ], poly(vinyl alcohol) (PVOH) [ 12 , 13 ], polybutylene(succinate) (PBS) [ 14 , 15 , 16 ], poly(butylene succinate-co-adipate) [ 17 , 18 , 19 ], and poly(butylene adipate-co-terephthalate) (PBAT) [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%